Intermediate skills in the workplace : deployment, standards and supply in Britain, France and Germany - Steedman, Hilary [Verfasser]; Mason, Geoff [Verfasser]; Wagner, Karin [Verfasser] (My University, 1991)
"The study is concerned with the level of supervisory and technician skills; on the basis of visits to factories and technical colleges in Britain, France and Germany, and analysis of labour force statistics, it compares and contrasts the provision and deployment of these intermediate skills in manufacturing industry in the three countries. At supervisory level only Germany undertakes a significant amount of training and to standards adequate to the increased complexity and technical demands of modern manufacturing. At technician (Higher National) level, the numbers acquiring comparable qualifications in Britain and France are substantially higher than in Germany: in part this reflects the allocation of a large proportion of technical support functions in German industry to craft-trained personnel. After examining the relative distribution of training costs between employers, individuals and the public authorities in the three conutries, the paper makes proposals for a more cost-effective mix of craft- and technician- level skills in British manufacturing which might, in the process, reduce the need for over-qualified personnel to 'plug the gaps' in skills among shopfloor workers and supervisors." (author's abstract) ((en)) Die Studie befasst sich mit der mittleren Qualifikationsebene von Aufsichtspersonen und Technikern im verarbeitenden Gewerbe. Im Rahmen einer Länderstudie werden Entwicklung und Struktur dieses "Zwischenbereiches" in Grossbritannien, Frankreich und der Bundesrepublik Deutschland verglichen. (IAB)
Die mittlere Qualifikationsebene am Arbeitsplatz in Grossbritannien, Frankreich und Deutschland
Keywords: G 1.2.3.1 Potenziale; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; G 2.3.1 Arbeitsteilung & -organisation; S 3.2 Unternehmen und Behörden; G 1.2.4.1.4 Verarbeitendes Gewerbe; S 1.3 Berufliche Erstausbildung; S 4 Kosten & Finanzierung; P 2.4 Facharbeiter / Gesellen; Qualifikation; Internationaler Vergleich; Mittlere Führungskraft; Techniker; Qualifizierung; Arbeitsverteilung; Facharbeiter; Meister; Verarbeitendes Gewerbe; Ausbildungskosten; Großbritannien; Frankreich; Bundesrepublik Deutschland; Quantitative Angaben